KONTRIBUSI KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DI INDONESIA - Nastiti Wahyu Pristianti; Rr. Iramani (Jurnal Ilmu Manajemen, 2022)
This study aimed to analyze the effect of company growth, activity ratio, profitability ratio, and dividend policy on the stock price of manufacturing companies on the Indonesian Stock Exchange period 2014-2018. Independent variables used in the study are company growth, Total Asset Turnover (TATO), Return on Assets (ROA), and Dividend Payout Ratio (DPR), while the dependent variable is the stock price. Sampling techniques were selected by purposive sampling of 176 manufacturing companies, and 53 companies were chosen as a sample. The data analysis technique used is multiple regression analysis. The result showed that simultaneous company growth, TATO, ROA, and DPR affect the stock price. TATO and ROA have a significant effect on the stock price. In contrast, the company growth and DPR has no significant impact on the stock price. Investors who want to invest in shares must also pay attention to the level of ROA, as this study states that ROA has the most significant influence on stock prices.